Study on Techniques to Defend Against Social Network Sybils - Rajeswari S, Mrs.; Priya C, Keerthi; P, Nikitha (IJRDO -Journal of Computer Science Engineering, 2016)
Unscrupulous users increasingly find Online Social Networking (OSN) platforms as lucrative targets for malicious activities, such as sending spam and spreading malware. The profitability of such activities and the fact that a large portion of the OSN communication takes place over social links (e.g., Facebook) that are symmetric in nature, motivate attackers to connect to real users. In particular, attackers take advantage of the open nature of OSNs and send to legitimate users unwanted friend requests, also known as friend spam.These friend spams have proven to be among the most evasive malicious activities